Correlation of thyroid function test with severity of liver dysfunction in cirrhosis of liver - Hasan, Md Rashidul; Shil, Bimal Chandra; Hossain, Jakir; Islam, Naylla; Saha, Dipannita; Hasan, Monirul; Chowdhury, Md Nahian Faruque (Bangladesh Journal of Medicine, 2024)
Background: A normal function of both the thyroid gland and the liver is necessary to maintain normal thyroid hormone levels and action. This study aimed to find out the thyroid abnormalities in patients presenting with liver cirrhosis and also to look for any correlation between thyroid function test (TFT) abnormalities and severity of liver disease. Methods: This cross-sectional observational study was conducted at the department of Gastroenterology and department of Medicine in Sir Salimullah Medical College, Dhaka, for 12-months. A total of 328 patients with liver cirrhosis were included after written informed consent. A detailed history, thorough laboratory and physical examination were carried out in each patient. Severity of liver dysfunction was graded by using Child Pugh Scoring. Thyroid function test was done. Data were collected in separate case record form and analyzed by SPSS 24.0. Results: According to Child Pugh score 31.1% had disease severity score A, 24.1% had B and 44.8% had C. Mean FT3 level (fmol/l) significantly decreases (5.3±1.5 in class-A, 3.5±1.7 in class-B and 3±1.3 in class-C) and TSH level (μIU/ml) significantly increases (3.3±1.3 in class-A, 5.3±2.1 in class-B and 5.5±1.8 in class-C) with increases number of disease severity score (p<0.05). Conclusion: There is a negative and inverse correlation between decreasing FT3 with severity of liver cirrhosis as measured by child pugh score and a positive and direct correlation between increasing Serum TSH with severity of liver cirrhosis as measured by child pugh score. This suggests that thyroid function test can be used as a prognostic indicator in cirrhotic patient. Bangladesh J Medicine 2025; 36: 25-31